2016
DOI: 10.21767/2386-5180.100068
|View full text |Cite
|
Sign up to set email alerts
|

Small Nettle: Evaluation of Its Anxiolytic Effect in the Elevated Plus-Maze and Open Field

Abstract: Background: Anxiety is a serious disorder affecting the world population. The most widely prescribed medications for anxiety disorders are the Benzodiazepines; however, they have prominent side effects. Thus, interest in alternative medicine that affects the 'mind' is growing. Among medicinal plants, Urtica urens has been recommended for relief of anxiety in Morocco folk medicine. Methods:The anxiolytic activity was evaluated with the adult mice by the elevated plus maze (EPM) and Open Field (OF) models of anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…in this study was non-sedating ( Supplementary Figure 3 ) and determined by the observed increase in beta activity ( Supplementary Figure 2 ). This setting dose of each drug is based on previous reports ( Brot et al, 1997 ; Doukkali et al, 2016 ; Shahnouri et al, 2016 ; Holmberg et al, 2018 ; Dornellas et al, 2020 ; Antonoudiou et al, 2022 ; Choudhary et al, 2022 ). Before a direct comparison study between these agents, we first investigated whether the SIT was suitable for evaluating antidepressant-like effects by administering escitalopram, a selective serotonin reuptake inhibitor (SSRI) antidepressant, to mice to examine whether it improved their social interaction.…”
Section: Resultsmentioning
confidence: 99%
“…in this study was non-sedating ( Supplementary Figure 3 ) and determined by the observed increase in beta activity ( Supplementary Figure 2 ). This setting dose of each drug is based on previous reports ( Brot et al, 1997 ; Doukkali et al, 2016 ; Shahnouri et al, 2016 ; Holmberg et al, 2018 ; Dornellas et al, 2020 ; Antonoudiou et al, 2022 ; Choudhary et al, 2022 ). Before a direct comparison study between these agents, we first investigated whether the SIT was suitable for evaluating antidepressant-like effects by administering escitalopram, a selective serotonin reuptake inhibitor (SSRI) antidepressant, to mice to examine whether it improved their social interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated Plus Maze (EPM) model [22][23][24][25][26] The Actophotometer test [27][28][29][30][31] The locomotor activity can be easily studied with the help of actophotometer, the rats were …”
Section: Screening For Antianxiety Activitymentioning
confidence: 99%